State Failure and Violent Regional Conflicts in Nigeria: The Niger Delta Ethnic Militias in Perspective - Tomwarri , Egeran; Igoli, Timipa (University of Nigeria Journal of Political Economy, 2024)
This paper examines the constraints of Nigerian federalism against the backdrop of the chronic resurgence of the ethnic Militias in the Niger Delta region, and the need of its reinvention to suit the exigencies of pluralism devoid of regional agitation. The paper interrogates the federalist idea and how it has failed to manage diversity of the Nigerian state. The implore secondary such of data collection. It adopted the frustration aggression theory to provide the foundation of the study and illustrate the causation between the independent and dependent variables to determine its effect. It also conceptualized the categories of militia in both Nigeria and other countries in a tabular form. It further elucidate the constraints of the region and how it has suffered under the dominance of the central government and the MNOCs, through their unwillingness to respond positively to the demands of the region. Therefore, the argument advanced is that the pitfalls have created an ungovernable space in the Nigerian federation for militia occupation, and been considered as the root cause of militancy in the region. The paper suggested that a federal state whereby the mechanism for dealing with such federalism has fractured or in the process of failing will facilitates militia manifestation, especially when the clearly stated conditions for the formation of the federation are breached by the system. Therefore, the paper concluded with suggested measure in curbing insurgency in the region.